2002
DOI: 10.17221/5841-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early nutritional experience on the feeding behaviour of adult female rats

Abstract: In the present paper the effect of postnatal undernutrition on feeding behaviour has been evaluated in mature female Wistar rats subjected to food restriction a) during the suckling period, i. e. up to day 15 (SR), b) during the weaning period from day 15 to 30 (WR), c) throughout 30 days post partum (SWR) and d) during adulthood, i. e. from day 60-75 of life (AR). In comparison with the ad libitum fed controls (C), the lactating mothers and the pups of the food-restricted groups were allowed free access to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, the animals whose dams were fed the energy restricted diet weighed more than the controls. Another study showed that female offspring of 50% calorie-restricted dams during the suckling period, although presenting a lower body weight than their controls, displayed increased food intake (Šefčíková and Mozeš, 2002 ). These conditions of undernutrition during the suckling period also affected feeding behavior in adulthood.…”
Section: Programming Effects Of Calorie Restriction During Lactation mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the animals whose dams were fed the energy restricted diet weighed more than the controls. Another study showed that female offspring of 50% calorie-restricted dams during the suckling period, although presenting a lower body weight than their controls, displayed increased food intake (Šefčíková and Mozeš, 2002 ). These conditions of undernutrition during the suckling period also affected feeding behavior in adulthood.…”
Section: Programming Effects Of Calorie Restriction During Lactation mentioning
confidence: 99%
“…These conditions of undernutrition during the suckling period also affected feeding behavior in adulthood. Evaluation of feeding behavior under different experimental conditions revealed that these rats consumed significantly less food in a new (unfamiliar) environment than in the home environment (Šefčíková and Mozeš, 2002 ).…”
Section: Programming Effects Of Calorie Restriction During Lactation mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, UG F1 virgins slightly increased food consumption and body weight through a balanced diet from PDs 25 to 90; however, they were unable to compensate the low body weight provoked by early undernutrition, which was associated with their maternal deficiencies and disrupted bonding interactions with the foster pups [16].…”
Section: Discussionmentioning
confidence: 99%